Role and mechanism of microRNA-21 in H2O2-induced apoptosis in bone marrow mesenchymal stem cells. (May 2016) - Lv, Chen; Hao, Yuehan; Han, Yaxin; Zhang, Wei; Cong, Lin; Shi, Yao; Tu, Guanjun
Highlights: microRNA (miR)-21 contributes to inhibition of apoptosis in bone marrow mesenchymal stem cells (BMSC). miR-21 down-regulates PTEN expression in BMSC. miR-21 inhibits apoptosis in BMSC at least partly via the PI3K/Akt pathway. LY294002 can abolish the protective effect of miR-21 on apoptosis in BMSC. Abstract: microRNA-21 (miR-21) contributes to anti-apoptosis, proliferation and migration in many cells, but its role in inhibiting apoptosis in bone marrow mesenchymal stem cells (BMSC) remains unclear. The aim of this study was to determine the role of miR-21 in H2 O2 -induced BMSC apoptosis. We used quantitative real time-polymerase chain reaction (RT-PCR) to demonstrate the level of miR-21 after treatment of BMSC with H2 O2 . BMSC apoptosis was induced by different concentrations of H2 O2 and was decreased in miR-21-upregulated cells. The expression of PTEN, a functional target gene of miR-21 in BMSC, was regulated by miR-21. The RT-PCR results indicated that miR-21 was significantly up-regulated, and western blot analysis indicated that Bcl-2 was up-regulated, whereas the apoptosis-related genes caspase 3/9 and Bax were down-regulated in miR-21-up-regulated cells. The miR-21-up-regulated cells had significantly enhanced Akt phosphorylation, as measured by western blot analysis. LY294002, an inhibitor of Akt activation, abolished the protective effects of miR-21-up-regulated cells. These results suggest that miR-21 contributes to inhibition of apoptosis in BMSC by down-regulating PTEN, potentially via the PI3K/Akt pathway.